Patience and the north-south divide in student achievement in Italy and the United States - Eric Alan Hanushek; Lavinia Kinne; Pietro Sancassani; Woessmann Ludger (EconPol Forum, 2024)
Human capital theory recognizes that time preferences - patience - are important for skill investments. We show how Facebook interests can be used to construct subnational measures of patience. Differences in patience are closely related to regional student achievement in Italy and the United States. They account for two-thirds of the achievement variation across Italian regions and one-third across US states. The results lead to new perspectives on long-standing within-country disparities.
Keywords: 330